E-Learning as A Learning Media Innovation Islamic Education - Hoerudin, Cecep Wahyu; Syafruddin, Syafruddin; Mayasari, Annisa; Arifudin, Opan; Lestari, Sisca (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
The use of technology in the digital era is an alternative way to maximize learning for students, especially distance learning. E-learning is a new model of learning in the digital era. This research aims to determine the extent of implementing e-learning based learning in Islamic religious education lessons in SKI learning at MAN Purwakarta. This type of research is a type of qualitative research with descriptive methods. The results of this research show that there are three functions of E-Learning as a learning medium: Additional Function, Complementary Function, and Substitute Function. Then, in the Islamic religious education learning process, the use of e-learning has three stages, namely the planning, implementation, and evaluation stages. The existence of E-learning makes it easier and faster to convey Islamic religious lessons even though there are still shortcomings. Human efforts to adapt to a learning system that continues to change is a concrete step in building an adaptive generation in every era.